The impact of cytomegalovirus infection and viral vector vaccination on human and mouse immune systems - Sharpe, HR (2021)
Viral vectors are a next-generation vaccine platform that elicit a robust response from the humoral and cellular arms of the immune system. The importance of this vaccine platform was demonstrated during this PhD with the emergence of SARS-CoV-2 and the development of the chimpanzee adenovirus-vectored vaccine ChAdOx1 nCoV-19. Although this vaccine is immunogenic, pre-existing infections such as cytomegalovirus have been shown to reduce antigen-specific vaccine immunogenicity in other vaccines. Cytomegalovirus is a chronic herpesvirus that is prevalent in ~40-100% adults worldwide, and although infection is often asymptomatic it can increase the frequency of terminally differentiated immune cells in healthy young adults.